PENGARUH KETERSEDIAAN INFRASTRUKTUR TERHADAP KETIMPANGAN PENDAPATAN DI PROVINSI JAWA BARAT - Siswantoro (CREATIVE RESEARCH JOURNAL, 2024)
West Java is ranked third as the province with the highest level of income inequality in Indonesia. Equitable infrastructure development is one strategy to reduce income inequality in a region. This research aimed to examine the impact of the availability of infrastructure in the form of roads, educational facilities and health facilities as well as a control variable in the form of economic growth on income inequality in West Java. A total of 189 panel data from 27 districts and cities over a period of 7 years (2016-2022) were evaluated using a selected regression model (random effect model). The data source taken from the West Java Province Statistics Agency. The research results showed that the availability of road infrastructure is the dominant factor in reducing income inequality in West Java rather than education and health facilities. This is possible because road infrastructure encourages connectivity between regions, develops other facilities more evenly and increases business productivity so that people's income increases and ultimately reduces income inequality.